Articulating viewpoints to better define and respond to the needs of adolescents and young adult survivors of pediatric brain tumors. Issue 3 (27th April 2022) - Bonanno, Marco; Bourque, Claude Julie; Aramideh, Jennifer; Cloutier, Nancy; Dumont, Émilie; Gomez-Tyo, Mathias; Julien-Lacoste, Ariane; Košir, Urška; Provost, Carole; Laverdière, Caroline; Sultan, Serge
Abstract: Purpose: Adolescents and young adult survivors of pediatric brain tumors (AYA-PBTS) often experience difficulties with social skills, pursuit of studies and employment. This study explored pediatric long-term survivors' perspective on their post-treatment needs and ways to improve resources and interventions. Methods: We used an original method of three sequential focus group interviews by adding the perspectives of survivors (15–22 years), parents and health professionals (total N = 22). Participants were recruited using purposive sampling from the long-term follow-up clinic at a Canadian tertiary hospital. We used computer-assisted analysis to draw themes from each group and compare thematic content across groups. Results: Categorization of participants' responses resulted in three domains: personal life, education and work. Participants mentioned the improvement of communication tools to facilitate access to timely information, the organization of counseling to improve employment integration, and tailoring interventions to optimize the return to daily activities in aftercare. Subsequent inductive analysis revealed three overarching trends among groups: multipurpose social networking, AYA-PBTS-specific information websites and transition tools and procedures. Conclusion and implications for psychosocial providers: This study identified solutions for AYA-PBTS' specific needs in aftercare. This population needs up-to-date post-treatment information and refined outreach procedures. Future research should define and prioritize these suggested solutions.